A WirelessHART and IEC 61850 Gateway Proposal - Covatti, Fernando; Winter, Jean Michel; Muller, Ivan; Pereira, Carlos Eduardo; Netto, João C. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2013)
Automation systems for monitoring and controlling power substations have received significant improvements through the implementation of IEC 61850 standard, which brought as the main advantage the interoperability between the different devices. However, there is still a gap in the use of wireless communication systems. The current standard does not adopt wireless communication options which allow low maintenance and installation costs. This paper proposes a solution for the integration of wireless communication technologies within the standard IEC 61850 attending the requirements of the power substations, such as reliability and security even in real-time applications.